PROFILE AND FINANCIAL BEHAVIOUR OF CRYPTO ADOPTERS – EVIDENCE FROM MACEDONIAN POPULATION SURVEY - Levkov, Nikola; Bogoevska-gavrilova, Irena; Trajkovska, Marija (Sciendo, 2022)
Regulators and policymakers in many developing countries are facing challenges on how to create opportunities for the crypto industry to grow, but at the same time protect investors and consumers. This study aims to better understand the demographic and socio-economic characteristics of crypto adopters and their financial behavior. Our study advances the knowledge within an array of recent contributions to the token economy and covers the geographical and contextual research gaps through survey data from a developing country in South Eastern Europe. We use descriptive statistics and chi-square analysis and we find that Macedonian crypto-adopters are more men of younger age, employed, with higher education and living in their own apartments in an urban area, and are mainly passive investors. We compare the findings with studies from other countries to provide valuable insights for policymakers and regulators.
Keywords: Crypto-adopters; cryptocurrencies; financial behavior; demographic profile; socio-economic profile